2020
DOI: 10.3390/ijerph18010031
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain and Teleworking in Times of the COVID-19: Analysis of the Impact on the Workers at Two Spanish Universities

Abstract: The special situation brought about by the coronavirus pandemic and the confinement imposed by the Government, has given rise to numerous changes in working habits. The workers at the universities have had to start a period of teleworking that could give rise to consequences for the musculoskeletal system. The objective of this article is to analyze the impact of the confinement on the musculoskeletal health of the staff of two Spanish universities. A cross-sectional, observational study was carried out on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 41 publications
(41 reference statements)
3
70
0
8
Order By: Relevance
“…About a third felt the same in the arm, forearm, hand, wrist, and shoulders. These results are consistent with studies conducted by international occupational health and safety organizations on the use of video display terminals [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…About a third felt the same in the arm, forearm, hand, wrist, and shoulders. These results are consistent with studies conducted by international occupational health and safety organizations on the use of video display terminals [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was determined by data related to temporary ergonomics that most of the respondents have worked more than 4 h per day for seven months, which means that workers are subjected to the probability of suffering from various health alterations in the future due to the intensive use of the video display terminal [ 16 , 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such musculoskeletal pain conditions are favorably affected by increased bodily activity [3][4][5]. Notably, recent epidemiological studies revealed that the current global confinement situation due to the COVID-19 pandemic initiated an increased frequency of moderate exercise, lowering the prevalence of musculoskeletal pain complaints [6,7]. The development of these chronic musculoskeletal pain states is potentially linked to central sensitization, (i.e., amplified transmission at central nociceptive neurons) [8,9], which is manifested by pain hypersensitivity [10] spreading heterotopically to sites beyond those directly affected by musculoskeletal input manipulation [11,12].…”
Section: Introductionmentioning
confidence: 99%